Behavior of R.C. beams with lap-spliced hybrid bars under flexure. Issue 1 (31st December 2023) - Hatem, Mohamed; Gnedy, Magdy; Helmy, Mohamed
ABSTRACT: The steel fiber-reinforced polymer composite bars Known as (SFCB) are new kind of reinforcement, for concrete structures. A layer of glass fibers and reinforced polymer surrounding the steel bars resulting in the (GFRP), when used as concrete reinforcement contributes for enough, serviceability strength, and durability. Increasing the elastic modulus of GFRP bar, which have function of protecting corrosion in addition to reduce the initial cost of the FRP bar, is the purpose of hybridization. SFCB has the advantages of being noncorrosive, nonmagnetic nonconductive, and light in weight, along with high strength. This study presents the behavioral characteristics of RC beams, with tensile lap-spliced steel fibers—coated bars under flexure. Ten beam specimens were tested, with concrete cross-section of (25*40*420) cm and compressive strength of 30 MPa. One beam specimen, (R) was taken as reference as it was reinforced with no lap splice. Nine beam specimens were divided into three groups. Group (A) contained three beam specimens reinforced with SFCB of diameter 16 mm and lap splice of 50φ, one with stirrups, without stirrups and with staggered lap splice. Group(B) contains three beams reinforced with SFCB of 16 mm diameter and lap splice of 55 φ one with stirrups, without stirrups and with staggered lap splice. Group(C) contains three beam specimens reinforced with SFCB of 16 mm diameter and lap splice of 60 φ one with stirrups, without stirrups and with staggered lap splice. Beams were exposed to pure flexure. Crack patterns and results are presented along with stress-strain curves. Finally, conclusions are summarized and presented.